Drag Kings in Cape Town: The performance of gendered subjectivities online - Shaikjee, Mooniq (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
The last few decades have seen the development of a large body of scholarly work on drag queens and performances of femininity by men (see Barrett 1995, 1999). However, performances of masculinity by women have largely been overlooked. Research by scholars like Judith Halberstam (1997, 1998) on female masculinity and the drag king performer has attempted to address this imbalance, but the phenomenon has yet to receive any attention from sociolinguists. This study aims to bring attention to online performances of masculinity by women in the South African context through a multimodal analysis of the Facebook pages of performers in the country’s first known drag king troupe, Bros B4 Ho’s. The study has three broad aims: firstly, to demonstrate the way in which the process of entextualisation is used as a key resource in the kings’ performances of masculinity online; secondly, to demonstrate that the masculinities put on display during these events are ‘queer subject position[s] that can successfully challenge hegemonic models of gender conformity’ (Halberstam 1997, 9); and thirdly, to argue that what the kings do is not always a straightforward disruption of heteronormative masculinity – at times they reproduce and reinforce the very structures they seek to critique.